The Antarctic krill Euphausia superba shows diurnal cycles of transcription under natural conditions - De Pittà C.; Biscontin A.; Albiero A.; Sales G.; Millino C.; Mazzotta G. M.; BERTOLUCCI, Cristiano; Costa R. (PLoS ONE, 2013)
Background: Polar environments are characterized by extreme seasonal changes in day length, light intensity and spectrum, the extent of sea ice during the winter, and food availability. A key species of the Southern Ocean ecosystem, the Antarctic krill (Euphausia superba) has evolved rhythmic physiological and behavioral mechanisms to adapt to daily and seasonal changes. The molecular organization of the clockwork underlying these biological rhythms is, nevertheless, still only partially understood. Methodology/Principal Findings: The genome sequence of the Antarctic krill is not yet available. A normalized cDNA library was produced and pyrosequenced in the attempt to identify large numbers of transcripts. All available E. superba sequences were then assembled to create the most complete existing oligonucleotide microarray platform with a total of 32,217 probes. Gene expression signatures of specimens collected in the Ross Sea at five different time points over a 24- hour cycle were defined, and 1,308 genes differentially expressed were identified. Of the corresponding transcripts, 609 showed a significant sinusoidal expression pattern; about 40% of these exibithed a 24-hour periodicity while the other 60% was characterized by a shorter (about 12-hour) rhythm. We assigned the differentially expressed genes to functional categories and noticed that those concerning translation, proteolysis, energy and metabolic process, redox regulation, visual transduction and stress response, which are most likely related to daily environmental changes, were significantly enriched. Two transcripts of peroxiredoxin, thought to represent the ancestral timekeeping system that evolved about 2.5 billion years ago, were also identified as were two isoforms of the EsRh1 opsin and two novel arrestin1 sequences involved in the visual transduction cascade. Conclusions: Our work represents the first characterization of the krill diurnal transcriptome under natural conditions and provides a first insight into the genetic regulation of ...